An eco-physiological study in relation to water use for tree growth of Eucalyptus camaldulensis and E. globulus on the dry west coast of South Africa - Gwaitta Magumba, David Andrew (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1998.